Thinking the Re-Thinking of the World Decolonial Challenges to the Humanities and Social Sciences from Africa, Asia and the Middle East - Kresse, Kai; Sounaye, Abdoulaye (ZMO-Studien, 2022)
As too many intellectual histories from the 'global South' remain under-explored, this book aims to redress such imbalance. Authors from the region sketch out their perspectives of transformations. This includes case studies and accounts from Africa, South Asia, and the Middle East. Taking a critical stance on the ongoing dominance of Eurocentrism in academia, the authors present their contributions in relation to current decolonial challenges.